2010
DOI: 10.1037/a0016112
|View full text |Cite
|
Sign up to set email alerts
|

Racial dialogues and White trainee fears: Implications for education and training.

Abstract: To assist educators in detecting the occurrence, understanding the dynamics, and effectively facilitating a difficult dialogue on race, we conducted a qualitative study to systematically examine the perceptions, interpretations, and reactions of 14 White trainees in counseling psychology graduate classes. In our focus groups, we identified 3 major domains: (a) global perspectives associated with race and racial dialogue, (b) specific reactions to racial disclosures, and (c) classroom strategies or conditions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 34 publications
3
105
0
1
Order By: Relevance
“…Studies have shown that when engaging in race talk in a classroom setting, White students responded to the topic with anxiousness and cautiousness because they were not only afraid to appear racist but also afraid of realizing they harbor racism, and wanted to avoid further conversation on the topic. Minority group students, on the other hand, became angry and frustrated as they felt a victim of microaggressions and were commonly stereotyped based on their skin color (Sue, 2013; Sue, Rivera, Capodilupo, Lin, & Torino, 2010). Goff, Steele, and Davies (2008) showed that Whites' interracial distancing (in this study, from Black conversation partners) was in fact not predicted by prejudice but it correlated with the “White racist” stereotype.…”
Section: Intergroup Concerns: Implications For Contact and Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that when engaging in race talk in a classroom setting, White students responded to the topic with anxiousness and cautiousness because they were not only afraid to appear racist but also afraid of realizing they harbor racism, and wanted to avoid further conversation on the topic. Minority group students, on the other hand, became angry and frustrated as they felt a victim of microaggressions and were commonly stereotyped based on their skin color (Sue, 2013; Sue, Rivera, Capodilupo, Lin, & Torino, 2010). Goff, Steele, and Davies (2008) showed that Whites' interracial distancing (in this study, from Black conversation partners) was in fact not predicted by prejudice but it correlated with the “White racist” stereotype.…”
Section: Intergroup Concerns: Implications For Contact and Attitudesmentioning
confidence: 99%
“…The current research investigates the phenomenon of pluralistic ignorance and related antecedents of contact, in the context of intergroup relations among a sample of Italian and immigrant adolescents in Italy. Avoiding intergroup contact can be damaging, especially in school settings as this is an impressionable time to form interracial acceptance (Al Ramiah et al, 2015; Sue et al, 2010). We, therefore, focus on educational settings and conduct our research with a sample of school students.…”
Section: The Current Researchmentioning
confidence: 99%
“…Our review found that perceived psychological distress in ethnic and racial minority groups (e.g., anxiety, diminished self-esteem, diminished self-efficacy, etc.) as the result of experiencing racial microaggressions has been documented in several settings, namely therapy (Constantine 2007; Crawford 2011; Morton 2011; Owen et al 2011; Schoulte et al 2011; Sue et al 2008a, b, c), clinical supervision (Barnes 2011; Beaumont 2010; Constantine and Sue 2007), academia (Cartwright et al 2009; Constantine et al 2008; Sue et al 2008, 2009, 2011), university classrooms and environment (Blume et al 2012; Gomez et al 2011; Granger 2011; Grier-Reed 2010; Robinson 2011; Sauceda 2010; Smith et al 2011; Sue and Constantine 2007; Sue et al 2009, 2010; Torres et al 2010; Yasso et al 2009), and the community (Burdsey 2011; De Oliveira Braga Lopez 2011; Huber 2011; Nadal 2008a; Nadal et al 2011b; Rivera et al 2010; Sue et al 2009; Wang et al 2011). However, only one study to date has explicitly explored the long-term effects of experiencing racial microaggressions (Torres et al 2010), and questions still remain regarding the cumulative effect of racial microaggressions across the lifespan.…”
Section: A Review and Critique Of Racial Microaggressions Literaturementioning
confidence: 99%
“…Expanding on this line of racial microaggression, research would help parse out the specific mechanisms in which racial microaggresions are processed and carried out. In addition, a few studies have explored racial microaggressions from the perspective of the offender (Doucette 2011; Henfield 2011; Sue and Constantine 2007; Sue et al 2009, 2010), each of which have indicated that offenders of racial microaggressions also experience psychological distress to some degree. This warrants explicit investigation of the type and degree of distress as well as other consequences of perpetrating racial microaggressions.…”
Section: A Review and Critique Of Racial Microaggressions Literaturementioning
confidence: 99%
“…In previous works, I have identified four White fears that resist dialectical change (Sue & Constantine, 2007;Sue, Rivera, Capodilupo, Lin, & Torino, 2010). It seems that for effective education and training to occur, there is a strong need to understand the fears and apprehensions first, before devising strategies for change.…”
Section: Challenges To Visibility: Toward Dialectical Movementmentioning
confidence: 99%